CONDENSATION OF REFRIGERANT R-407C INSIDE HORIZONTAL FINNED TUBES - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
This paper provides plan experiment of heat transfer and pressure drop during condensation of refrigerant R-407C inside horizontal finned tubes. The substitution of traditional refrigerants, and particularly of R-22 (chlorodifluoromethane), can call for the use of zeotropic 'mixtures of HFCs with zero ODP (ozone depleting potential). R-407C is one of the replacement candidates for R-22. Due to its zeotropic nature, the heat transfer coefficient during condensation of R-407C inside a horizontal tube is much lower than that for R-22. Various types of finned tubes have been developed to enhance condensation of refrigerants inside horizontal tubes. However, no theoretical model is currently available that can be used to optimize the fin geometry for condensation of R-407C. The goal of the research is to develop a theoretical model for predicting the heat transfer and to develop an empirical correlation for the pressure drop during condensation of R-407C inside a horizontal finned tube.